Dry matter, carbon and nitrogen of soybean and corn roots in conventional tillage and no‑tillage systems - Bordin, Ivan (2009)
The objective of this work was to examine whether soil tillage systems affect the distribution and accumulation of dry matter (DM), carbon (C) and nitrogen (N) of root systems of soybean (Glycine max) and corn (Zea mays) in a clayey Typic Haplorthox. Volumetric rings were used for root sampling down to 1 m depth. The distribution in depth and accumulation of DM, C and N of soybean and corn roots were not affected by soil tillage systems. Root length density was 0.7–1.4 cm cm-3 for soybean and 1.2–1.6 cm cm-3 for corn in the 0–0.10 m layer and decreased in the other layers. Root DM input was 1.94–2.01 Mg ha-1 in soybean and 2.50–3.79 Mg ha-1 in corn. For soybean, C and N root inputs were 0.61–0.63 Mg ha-1 and 36.9–38.2 kg ha-1, respectively. For corn, C and N root inputs were 0.72–1.10 Mg ha-1 and 18.78–28.48 kg ha-1, respectively. Independently of the tillage system, 80% of the roots were concentrated in the upper surface layer 0.43 to 0.54 m deep for soybean and in the upper surface layer 0.40 to 0.46 m deep for corn.